2014
DOI: 10.6007/ijarbss/v4-i12/1362
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Spirituality as a Determinant of Organizational Commitment amongst Academic Staff in the Private and Public Universities in Kenya

Abstract: This study focused on workplace spirituality an intrinsic factor as a determinant of organizational commitment although most recent studies on organizational commitment have focused mostly on the extrinsic rewards such remuneration, training opportunities, promotion and other tangible monetary benefits as predictors of organizational commitment. Employees are viewed as one of the most important assets for most organizations, in particular servicebased organizations like universities because of the benefits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 17 publications
(11 reference statements)
0
22
0
2
Order By: Relevance
“…A study by [19] found that employee participation in decision making significantly influences university academic staffs" organizational commitment in Kenya.…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…A study by [19] found that employee participation in decision making significantly influences university academic staffs" organizational commitment in Kenya.…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Wainaina [23] conducted a research about effect of teachers' participation in decision making on the organizational commitment amongst academic staff in the private and public universities in Kenya and found that decisions made in consultation with teachers are more effective. Particularly, those teachers who are involved in decision-making are better equipped to implement such decisions.…”
Section: Teachers' Participation In Decisionmakingmentioning
confidence: 99%
“…It involves having a deep sense of meaning and purpose in one's work [27]. Meaningful work represents how employees interact with their day-to-day work at the individual level [28]. Providing a deeper sense of meaning and purpose for employees is important, as this enables employees to perform better and to be more productive and creative at work.…”
Section: Workplace Spiritualitymentioning
confidence: 99%